Previous injury and lower well-being increase injury risk in female adolescent athletes - Ekenros, L.; Fridén, C.; von Rosen, P. (International Journal of Sports Medicine, 2023)
Several risk factors for injury have been suggested in female elite athletes. However, there is a lack of prospective studies in young female athletes where multiple risk factors have been studied. The aim of this study was to identify risk factors for injury in female adolescent elite athletes. Substantial injuries were monitored in 222 athletes using the validated Oslo Sports Trauma Research Centre Questionnaire over 20 weeks. Over 20 potential risk factors were explored. Based on a binomial generalized linear mixed model, two significant (p<0.05) risk factors for injury were identified; previous injury within the last 12 months (OR 2.55) and well-being (OR 0.97). An athlete with a previous injury had twice as high a risk of injury (13% vs. 6%) compared to an athlete with no previous injury. Higher perceived well-being was associated with a decreased risk of injury. Based on a prospective design with a large sample of female adolescent elite athletes, investigating over 20 potential risk factors for injury, our results suggest that a previous injury and well-being are risk factors for injury.